Analysis of the Impact of Work Interaction, OSH Culture, and Motivation on Employee Performance (A Case Study on a Mining Company) - Rudy Suprapto; Isti Fadah; Rini Yayuk Priyati; Indrianawati Usman (Journal of International Conference Proceedings, 2022)
Interactions between employees who have various backgrounds, employee motivation and safety culture are parts of a chain and integrated aspects to achieve a good employee performance. This study to analyze the effect of work interaction, safety culture and work motivation on employee performance at the Department of Underground Maintenance, PTFI, Papua, Indonesia. This research is explanatory research, that explains the causal relationship between the study variables and hypothesis testings. The study shows that there are significant and simultaneous effects of work interaction, OSH culture and work motivation on employee performance at the Department of Underground Maintenance. Moreover, work motivation variable gives dominant effect to performance within the department.Â Keywords: Employee Performance, OSH/Safety Culture, Work Interaction, Work Motivation.